The Challenge of Improving Special Education Quality in Digital Era - Mega Iswari (Department of Special Education, 2019)
Digital era is a term used in the internet network technology, especially information technology. Today, the learning process is highly developed and predictably rapid; therefore, teachers should be more proficient in using digital technology because they will use it to teach the students. In education for students with special needs which is still conducted conventionally, the process of administrative, financial, academic, and learning methods need changes along with the development of information and communication technology. Therefore, the education requires ongoing innovation, technology, resources of professional educators which are digitalized.